The Logic of Sociability in the Scottish Enlightenment: Thomas Reid’s Social Operations of Mind1 - Ivana Dragoş (American, British and Canadian Studies Journal)
This article sheds light on the logic of sociability in the Scottish Enlightenment, which has been regarded as a characteristic mode of thought and action, given the authoritative influence of David Hume’s “Science of Man” (1739). Hume’s “Science” focuses on the interaction between the moral self and other fellow beings able to display feelings of sympathy and thus to participate in the moral good and wellbeing of civil society. Hume’s influential argument left a legacy to other Scottish Enlightenment philosophers, among them being Thomas Reid, one of his well-known opponents, who was the first to coin and discuss “the social operations of mind.” The article seeks to provide an overall epistemological account of “social operations,” with particular focus on the act of promising and testimony. Opposed to “solitary operations” (cf. Reid), “social operations” become successful if and only if their expression by words or signs elicits the addressee’s reaction understood as the latter’s choice to accept it or not. In the case of testimony, I will show how Reid’s argument – sometimes paradoxical or contradictory – cannot get rid of judgement or reasoning when it comes to checking the veracity of what is testified, on the one hand, and of what is to be believed, on the other.